What to do when doctors disagree on diet for women with Gestational Diabetes - Kolasa, Kathryn M.; Haven, Kelley; Craven, Kay (My University, 2018)
Medical nutrition therapy is considered the cornerstone of treatment for gestational diabetes mellitus, even though there is no consensus on the best dietary approach to achieve optimal glycemic control and positive maternal and fetal outcomes. In this article, we present a case from our clinic of a woman with gestational mellitus, the evidence for the level of macronutrients to include in the diet, and the use of glycemic index for dietary planning. We also review the evidence for emerging dietary therapies and provide general recommendations that should be individualized to the patient.
Keywords: gestational diabetes diet carbohydrates